2008
DOI: 10.1099/jmm.0.2008/001917-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and dissemination of the Ser315Thr substitution within the KatG enzyme in isoniazid-resistant strains of Mycobacterium tuberculosis isolated in Uruguay

Abstract: The aim of this study was to determine the prevalence of Ser315Thr substitution in isoniazid (INH)-resistant strains of Mycobacterium tuberculosis in Uruguay. The katG gene of 62 INH-resistant strains was analysed by an RFLP-PCR assay. PCR products were digested with MspI to detect Ser315Thr and Arg463Leu substitutions. A total of 16 of the 62 (26 %) INH-resistant strains analysed had a Ser315Thr substitution. Only one INH-resistant strain had an Arg463Leu substitution and two strains had a deletion in katG. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…A high clustering proportion of katG 315Thr allele was observed in this study. This allele was associated with MDR-TB as reported elsewhere [18], [31], [32]. Therefore, this allele may be the major genotype responsible for the recent transmission of MDR-TB and INH resistant strain in the studied areas.…”
Section: Discussionsupporting
confidence: 78%
“…A high clustering proportion of katG 315Thr allele was observed in this study. This allele was associated with MDR-TB as reported elsewhere [18], [31], [32]. Therefore, this allele may be the major genotype responsible for the recent transmission of MDR-TB and INH resistant strain in the studied areas.…”
Section: Discussionsupporting
confidence: 78%
“…The predominance of 315 mutations in the katG gene in INH R clinical isolates has been documented in several studies, with observed frequencies ranging between 30% and >90%. In countries such as Scotland, Spain, Italy, and Uruguay [ 25 28 ] the prevalence of INH R strains with S315T substitution was found to be relatively low (20–50%). Studies from countries like Netherlands, India, Africa, China, and Dubai have reported moderate levels of prevalence of the 315 substitutions, ranging between 50 and 70% [ 16 , 18 , 19 , 29 – 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mutation in katG gene occurs in a 100 fold higher frequency than rpoB gene 9 and is regarded as first step in evolution of MDR-MTB [10][11][12][13] and also creates more possibility for acquiring mutations in other genes. [13][14][15] The combination of INH resistance and maintained virulence might make it possible for some INH resistant strains, especially those with the katG Ser315Thr mutation, to acquire extra drug resistance and become MDR-TB. 13 The molecular basis of resistance to isoniazid is more complex and is caused by a variety of mutations in four different genes of MTB i.e.…”
mentioning
confidence: 99%